Origin stories: Framing 25 years of Dutch political discourse on child sexual exploitation by tourists and travelers - Koning, Anneke (European journal of criminology, 2024)
Sexual exploitation of children in the context of travel and tourism (SECTT) has been described as a serious and growing problem. This study critically analyzes political debates and policy measures proposed by the Dutch government between 1995 and 2020 to combat SECTT. To understand how SECTT is framed in Dutch political discourse, Bacchi's ?what's the problem represented to be?? approach guided a systematic critical discourse analysis of over 200 political documents. Our analysis shows that SECTT has, over time, predominantly become framed as a crime problem. Offender detection, international cooperation, awareness raising, public?private partnerships, and prevention targeted at known sex offenders are the most commonly proposed solutions. Despite the focus on apprehending offenders, the political discourse offers no concrete clues as to who they are; still, conducting research or evaluating policies' effects is seldom proposed as a response. This problem representation overlooks the connections of SECTT with structural issues, such as victim vulnerabilities, colonization, and global inequality on the one hand, and mental health, sexual expression, and cultural values on the other.